A Software Reuse Paradigm for the Next Generation Network (NGN) - Jagot, Bilal Abdull Rahim (My University, 2006)
Service creation in the Next Generation Network (NGN) is focused around software creation and borrows heavily from the Software Engineering community. In the NGN, telecommunication companies demand simple, rapid and economical service creation. The key to this type of service creation is software re-use. Software re-use is a conundrum where limited, dedicated solutions exists. These solutions include amongst others Enterprise JavaBeansTM (EJBs), design patterns and object-oriented programming. The Telecommunications Information Networking Architecture- Conformance And Testing (TINA-CAT) workgroup has done work on a functionality centric concept called RP-facets. This report proposes a redefinition of RP-facets, as Facets, for software re-use across the design and code level. We redefine Facets as functionality centric reusable components. A Facet is independent of the implementation language and the execution platform. Facets allow containment in a structured manner via a user defined Facet Hierarchy. Facets are resource, context and data agnostic. They also introduce a structured way to allow source code to be changed based on design level decisions. Also, possessing the ability to allow the simultaneous use of other reuse solutions and programming paradigms. Abstraction of detail from developers and platform migration can be achieved by using Facets. Facets are composed of a Generic definition and any number of Implementation definitions. The definitions are supported by an underlying informational model called meta-¼. Meta- ¼ is a model at the M3 meta-level that focuses on describing entities. Most of the Facet’s capabilities are enabled by the meta-¼ model. An environment for developing Facets is created, called the Facet Development Environment (FDE). The Facet Developer (FD) role is introduced to develop and maintain Facets. The FD verifies programmes from programmers to be included into the catalogue of Facets via the FDE. The FD interacts with service creation teams to determine which Facets can be used in the service they wish to develop. Facets prove their capability in targeted areas, yet lack in other categories. It is recommended that the underlying informational model should be revised to form a more robust and flexible entity describing model. In addition, a cataloging capability to easily find Facets with particular functionality should be appended to the capabilities of the facet. It is proposed, for future work, that a development environment be created that encompasses a process for using Facets to create services.
MSc thesis - Faculty of Engineering
Keywords: Service creation; Next Generation Network; NGN; Software Engineering; software re-use; Facets; reusable components; Facet Development Environment; FDE